Analysing EFL Students’ Approach to Translating English Advertisements - Alowysa Br Purba; Irene Gultom; Krismardo Gea; Delsianti Dohude; Jamaluddin Nasution (ELT Worldwide: Journal of English Language Teaching, 2022)
Translation is critical for second language acquisition in an EFL setting, much more so for people who cannot speak or understand a foreign language. Additionally, translation can aid in the educational process, particularly for elementary, junior high, and high school students. Students who are capable of precise translation will be more receptive to global knowledge, will improve their skills, and will have an open mind. Then they may think creatively and generate fresh insights and ideas. The purpose of this study is to determine the translation ability of Indonesian junior high school students when it comes to translating English ads. The current study adopts a qualitative descriptive methodology. The samples consisted of 25 grade VIII students from SMP Negeri 21 Medan. The findings discovered eight methods discussed and analyzed by the researchers. The results indicated that users of the literal method were the method which was most widely used by students with 96% of students using this method, and second was the free method with 88% of users, the third was the addition method with 72%, while fourth was the omission method with 36%, fifth position was the paraphrase method, and in the sixth to the eighth method was the explication method, the generalization method, and the concretization method respectively with each use of 0% or none used by students. The result of the research shows that the use of the literal method is more dominantly used by students and is easier to understand by students, and for other methods there are still some that have not been studied by students. Therefore, students need to continuously improve their English-speaking skills and increase their vocabulary. In addition, students also needed to learn the translation method as an important guide in carrying out translation activities.